A Legal Certainty Perspective On The Status of Notarial Deeds Not Recorded In The Repertorium - Charisma Budiman, Firduas; Sentot Sudarwanto, Albertus; Ismunarno, Ismunarno (International Journal of Educational Research & Social Sciences, 2025)
A notarial deed is a legally binding instrument with full evidentiary value in the Indonesian legal system. Its presence is crucial to ensuring certainty, order, and legal protection for all parties. A primary duty of notaries is to record every deed in the repertorium, as required under Articles 58 and 59 of the Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 on the Notarial Office (UUJN). The repertorium, part of the notarial protocol, must be submitted periodically to the Regional Supervisory Council as proof of accountability. In practice, however, some deeds remain unregistered, creating issues regarding their legal standing, certainty for the parties involved, and the notary’s responsibility. This study applies a normative juridical method with statutory, conceptual, and case approaches. Data are drawn from regulations, doctrines, court decisions, and legal literature. The analysis emphasizes Gustav Radbruch’s theory of legal certainty and its relevance to deed registration, particularly the juridical consequences of unregistered deeds. Findings reveal that while unrecorded deeds remain authentic if formal requirements are met, the lack of registration weakens accountability and may reduce evidentiary strength in court. Notaries failing to comply may face administrative sanctions under Article 65A UUJN, from warnings to temporary dismissal. Registration, therefore, is not merely administrative but essential to uphold certainty, justice, and the integrity of the notarial profession.